Polar low developed in the Norwegian Sea on 25 March 2019 – Simulations with the Canadian Regional Climate Model (CRCM6/GEM4) and manual track - Moreno-Ibáñez, Marta; Laprise, René; Gachon, Philippe (Borealis, 2023)
This dataset contains: 1. The output of an ensemble of simulations of a polar low that developed over the Norwegian Sea on 25 March 2019. 2. The manually-obtained tracks of the polar low. 1. Simulation output The simulations of the polar low were conducted with the convection-permitting Canadian Regional Climate Model version 6 (CRCM6/GEM4) driven by the reanalysis ERA5. The model has a grid mesh of 0.0225° and a vertical grid with 62 levels. The size of the model domain is 1004 x 1004 grid points, excluding the sponge zone, and the model top is at 2 hPa. The model was initialised every six hours from 23 March at 0000 UTC to 24 March at 1800 UTC, and the end date of the simulations was 26 March at 0600 UTC. This dataset contains the hourly output of these eight simulations. The 2D fields include several variables at screen level (temperature, dewpoint temperature, relative humidity, horizontal wind, wind gust) as well as sea level pressure,1 h accumulated precipitation, and surface sensible and latent heat fluxes. The 3D fields are geopotential height, temperature, relative humidity, horizontal wind, and the vertical velocity in pressure coordinate, and they are provided on 22 pressure levels from 1,000 to 10 hPa. 2. Polar low tracks This dataset contains the different tracks of the polar low that have been obtained using the observations, the reanalysis ERA5 and the output of the eight simulations. The data provided are the time, latitude and longitude of the track points, as well as the sea level pressure minimum. For the track obtained using observations, the dataset also includes the distance between the track point and the closest surface station (which is the one that provides the value of the sea level pressure minimum). Only the sea level pressure observations from stations within 25 km from the PL centre are included.
Keywords: Gachon_Philippe